DIAGNOSIS AND MANAGEMENT OF LEPROSY ON CHILDREN − REGARDING A CASE - Ana Cecília Studart Prata; Gisele Reis Cunha Silva; Márcio Mendes; Thais de Lima Tourinho; Verônica Vilas-Bôas Ferrari; Rodrigo Neves Santos; Fred Bernardes Filho; Maria Vitória Pinto Quaresma Santos; José Augusto da Costa Nery (Journal of the Portuguese Society of Dermatology and Venereology, 2014)
Leprosy is an endemic disease in Brazil and constitutes a serious public health problem. The delay in diagnosis and treatment can lead to irreversible sequelae. In children, the diagnosis requires a careful scrutiny, given the difficulty of implementation and interpretation of sensibility testing. The treatment in this age group demands attention, with adequate doses of anti-leprosy drugs to the patient's weight, a factor that contributes to the reduction of adverse effects and promotes adherence to treatment. The authors present a case of tuberculoid leprosy in a 3 year old child and discuss the multidrug therapy recommended by Brazil’s Health Ministry.